Lighting up the photon Wigner distribution via dilepton productions - Yu Shi; Lin Chen; Shu-Yi Wei; Bo-Wen Xiao (Physics Letters B)
We present a systematic investigation of lepton pair production through photon-photon fusion processes in heavy-ion collisions. It is demonstrated that the dilepton production at a given impact parameter (b⊥) with a fixed transverse momentum imbalance (q⊥) can be factorized into a unified formula in terms of the Wigner photon distribution of heavy nuclei. We show that this framework provides a comprehensive description of all the relevant data from RHIC to the LHC, with a strong evidence that the quasi-real photon can be radiated not only from the nucleus as a whole, standing for the coherent contribution, but also from the sub-structures inside the nucleus, representing the incoherent contribution. Further predictions are made for the anisotropies in the correlations between q⊥, b⊥, and the dilepton transverse momentum (P⊥). This will help us to constrain the photon Wigner distribution which plays a crucial role to study the gluonic matter of nucleus at small-x through the diffractive photoproduction processes in heavy ion collision.